(untitled) (Journal of Bio-Science, 2011)
Context: Fumonisin B1 (FB1), a mycotoxin produced by Fusarium verticillioides and other Fusarium species that grow on maize worldwide, has been documented to cause various physiological responses in animals. Consumption of lesser amounts of fumonisins at levels below those that cause overt toxicity may exert haematological, serum biochemical and/or histopathological effects in animals. Objective: The effects of dietary FB1 on haematology, serum biochemistry and histopathology were assessed in female Wistar rats in a short-term toxicity study. Materials and Methods: Thirty-nine mature female Wistar rats (Rattus norvegicus) weighing between 167.5 – 170.5 g were used in the study. The rats were assigned to diets containing 0.2, 10.0 and 20.0 mg FB1/kg constituting diets 1, 2 and 3, respectively. After 14 days of feeding, blood samples were obtained from four rats per treatment. The rats were sacrificed by cervical dislocation, eviscerated for organ collections and subsequently processed for histology. Results: Significant differences in feed consumption and body weight gains were not observed. The final live weight of the rats, however, seemed to decline with an increase in dietary FB1 levels. Significant (P<0.05) alterations were observed in the haematological and serum biochemical parameters with increasing levels of dietary FB1. Diets containing different FB1 concentrations, the decreased values of PCV, Hb, erythrocyte and monocyte counts could be attributed to the FB1 effects on the blood-forming tissues in animals placed on diets 2 and 3 as compared to those fed diet 1. Also, histopathological changes were observed in the livers, kidneys, spleens and hearts of rats fed diets 2 and 3. Conclusion: This study revealed that the No-observable adverse effect level (NOAEL) of dietary FB1 above which may cause significant physiological changes without overt toxicity for short-term toxicity study in female Wistar rats is <0.74 mg/kg bw per day. Keywords: Blood; Rat; Mycotoxin; Fusarium verticillioides; Fumonisin B1; Histopathology. DOI: http://dx.doi.org/10.3329/jbs.v18i0.8779 JBS 2010; 18(0): 74-83